YAVUZ SULTAN SELİM’İN ŞEHZÂDELİK DÖNEMİ (1487-1512) - (:unkn) unknown (My University, 2019)
Bu makalede Yavuz Sultan Selim’in şehzadelik dönemi (1487-1512) elealınmıştır. Öncelikle doğumu, eğitimi, sünnet düğünü, hocaları, annesi, kardeşleri,hanımları, kız ve erkek çocukları hakkında yeni bilgiler tespit edilmiş;ardından uzun yıllar sancak beyliği yaptığı Trabzon’daki faaliyetleri incelenmiştir.Bu manada Trabzon’daki idarî ve malî icraatları; imar, iskân vekültür faaliyetleri; Gürcistan ve Safevîler’e yönelik seferleri arşiv vesikalarıve devrin kaynaklarına istinaden ortaya konulmuştur. Oğlu Şehzâde Süleyman’asancak verilmesi için sergilediği mücadele ile Trabzon sancak beyliğiesnasında Kefe’ye geçerek başlattığı taht mücadelesi ve bu süreçte babası,kardeşleri ve İstanbul’daki bir kısım devlet ricaliyle yaşadığı çatışmalar elealınmıştır. Gerek Trabzon sancak beyliği sırasında maiyetindeki görevlilerve gerek taht mücadelesi esnasında kendisine yardımcı olan idareci ve askerlerleilgili ayrıntılı bilgiler verilmiştir. Böylece Yavuz Sultan Selim’in şehzadelikdönemi ve onu tahta hazırlayan gelişmeler orijinal bilgilerle etraflıcatahlil edilmiştir.

This article covers the principality period (1487-1512) of Selim I. Firstly, new information has been revealed about his birth, education, circumcision ceremony, teachers, mother, siblings, wives, daughters and sons; then during his governing of sanjak for a long time in Trabzon his policies were analyzed. In this sense, administrative and financial policies; settlement and cultural activities and military campaigns towards Georgia and Safavid state have been presented referring to archive documents and such period-sources. In addition, it was mentioned about his struggle for his son, the Prince Suleyman, to be given a sanjak and and during his principality of Sanjak in Trabzon, his transition to Kefe and starting a struggle for the throne and his confrontation against his father, brothers and some high officials in Istanbul in this process. Information about the servants who worked for Yavuz Sultan Selim and administrators and soldiers who assisted himself during the throne struggle have been given in detailed. As a result, this article has critically analyzed the period of his own principality and some events until ascending to throne, with original information.
“Prıncıpalıty Perıod Of Selım I (1487-1512)”
Keywords: Tarih